Menelusuri Pengaruh Kreativitas Hijau Karyawan terhadap Kinerja Hijau melalui Perilaku Hijau Sukarela - Yusniar Lubis; Wan Suryani; Siswa Panjang Hernosa; Fajar Rezeki Ananda Lubis; Nasib Nasib (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study aims to analyze the effect of employee green creativity on green performance through voluntary green behavior at Hotel Grand Aston Medan. A quantitative approach was employed, utilizing a survey method with 150 hotel employees conducted during 2023. The data were analyzed using path analysis to test the relationships between variables. The results indicate that employee green creativity has a significant direct effect on both voluntary green behavior and green performance. Furthermore, voluntary green behavior was found to be a significant mediator between employee green creativity and green performance. These findings highlight the importance of employee creativity in generating environmentally friendly solutions, which in turn contribute to enhancing the hotel’s green performance. This study provides strategic insights for the management of Hotel Grand Aston Medan to improve sustainable performance by empowering employee creativity and voluntary green behavior.